2012
DOI: 10.1242/jeb.072314
|View full text |Cite
|
Sign up to set email alerts
|

Leg adjustments during running across visible and camouflaged incidental changes in ground level

Abstract: SUMMARYDuring running in a natural environment, humans must routinely negotiate varied and unpredictable changes in ground level. To prevent a fall, changes in ground level, especially those that are invisible, require a quick response of the movement system within a short time. For 11 subjects we investigated two consecutive contacts during running across visible (drop of 0, 5 and 10cm) and camouflaged (drop of 0 and 10cm) changes in ground level. For both situations, we found significant variances in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 31 publications
4
79
0
Order By: Relevance
“…Previous studies have shown that during running across visible and camouflaged drops in ground level, humans extend their ankle joint before touchdown (Müller et al, 2012a). With this study, we wanted to investigate the neuro-mechanical strategy responsible for the increased plantar flexion angles at touchdown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that during running across visible and camouflaged drops in ground level, humans extend their ankle joint before touchdown (Müller et al, 2012a). With this study, we wanted to investigate the neuro-mechanical strategy responsible for the increased plantar flexion angles at touchdown.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, changes in flight time will be small. In contrast, during running across camouflaged drops of −10 cm, it seems that runners anticipate a drop of about 5-10 cm (Müller et al, 2012a). The absence of the expected contact (CD10) results in increased flight time.…”
Section: Research Articlementioning
confidence: 96%
See 3 more Smart Citations